Heather, the violet fairy - Meadows, Daisy; Ripper, Georgie (New York : Scholastic, 2003)
A merry-go-round sends Rachel and Kirsty to a magical world. Did Heather, the violet fairy have anything to do with this?
"A Little Apple paperback."
2.
006-009.
Accelerated Reader AR
Keywords: Fairies -- Juvenile fiction; Merry-go-round -- Juvenile fiction; Colors -- Juvenile fiction; Fairies -- Fiction; Merry-go-round -- Fiction; Color -- Fiction; Fantasy; Fantasy fiction